2023
DOI: 10.1515/jcim-2022-0247
|View full text |Cite
|
Sign up to set email alerts
|

Reporting of adverse effects of pomegranate in clinical studies: a systematic review

Abstract: Objectives Numerous studies have shown the pharmacological effects of pomegranate, such as: anti-cancer, cholesterol-lowering, anti-diabetic, and antihypertensive features. Pomegranate consumption has also revealed some adverse effects. This systematic review aimed to explore the adverse effects of pomegranate reported in clinical studies. Content The keywords “pomegranate”, “Punica granatum”, “side effect”, “clinical trial”,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…A systematic review ( Zare et al, 2023 ) analyzed the adverse effects reported in clinical studies of pomegranate, including a total of 66 clinical articles. This review indicates that pomegranate and its extracts are generally safe, with few reported side effects, primarily gastrointestinal issues and allergic reactions.…”
Section: Current Research and Prospectsmentioning
confidence: 99%
“…A systematic review ( Zare et al, 2023 ) analyzed the adverse effects reported in clinical studies of pomegranate, including a total of 66 clinical articles. This review indicates that pomegranate and its extracts are generally safe, with few reported side effects, primarily gastrointestinal issues and allergic reactions.…”
Section: Current Research and Prospectsmentioning
confidence: 99%